2018
DOI: 10.1371/journal.pone.0195237
|View full text |Cite
|
Sign up to set email alerts
|

The ties that bind: Ingroup ties are linked with diminished inflammatory immune responses and fewer mental health symptoms through less rumination

Abstract: The present research explored whether components of social identity, namely ingroup ties, affect, and centrality, were differentially linked to mental health and inflammatory immune responses, and whether rumination mediated those relations. Study 1 (N = 138) indicated that stronger ingroup ties were associated with fewer mental health (depressive and post-traumatic stress) symptoms; those relations were mediated by the tendency for individuals with strong ties to rely less on ruminative coping to deal with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 87 publications
4
12
0
Order By: Relevance
“…The finding that Collective Need for Inclusion contributes to well‐being also corroborates the so‐called “social cure hypothesis”, which holds that group identification can lead to higher levels of psychological and even physical well‐being (e.g., Haslam et al, ; Ysseldyk, McQuaid, McInnis, Anisman, & Matheson, ). As a strong Collective Need for Inclusion is likely to motivate people to search for membership to and identify with social groups, they can be expected to reap the benefits of group membership and identification, which is, among others, an increased level of well‐being.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The finding that Collective Need for Inclusion contributes to well‐being also corroborates the so‐called “social cure hypothesis”, which holds that group identification can lead to higher levels of psychological and even physical well‐being (e.g., Haslam et al, ; Ysseldyk, McQuaid, McInnis, Anisman, & Matheson, ). As a strong Collective Need for Inclusion is likely to motivate people to search for membership to and identify with social groups, they can be expected to reap the benefits of group membership and identification, which is, among others, an increased level of well‐being.…”
Section: Discussionsupporting
confidence: 64%
“…The finding that Collective Need for Inclusion contributes to well-being also corroborates the so-called "social cure hypothesis", which holds that group identification can lead to higher levels of psychological and even physical well-being (e.g., Haslam et al, 2009;Ysseldyk, McQuaid, McInnis, Anisman, & Matheson, 2018). As a strong…”
Section: Collective Inclusion Needs As a Relevant Variable For Our supporting
confidence: 71%
“…The more participants identified with their social group (family/friends and work group, respectively), the more social support they perceived themselves as receiving, the higher they rated their life/job satisfaction, and the lower they rated their stress levels. Further evidence for the important effects of social identity processes on secondary appraisal is provided by Ysseldyk, McQuaid, McInnis, Anisman, and Matheson (), who showed that ingroup ties were negatively associated with the use of ruminative coping to deal with stressful events, which in turn was negatively associated with stress‐related inflammatory immune‐system responses. Together, these findings suggest that group identification can shield people from the negative effects of stress, allowing them to feel more able to cope.…”
Section: Early Work: Social Group Memberships and Stress Appraisalmentioning
confidence: 99%
“…Therefore, this study supports the idea that interacting with other people in an ABG can reduce negative affect by diverting attention away from rumination Ysseldyk et al, 2018). Furthermore, people with CMHC also reported preferring to talk to other people or doing something active to improve their emotional state than withdrawing or being alone.…”
Section: Emotion Regulation In Arts-based Groupssupporting
confidence: 78%
“…This research built on a growing body of social cure research for mental health, which has demonstrated that meaningful group identities can prevent the development of mental health problems (Miller, Wakefield, & Sani, 2015;Saeri, Cruwys, Barlow, Stroge, & Silbey, 2018;Ysseldyk, McQuaid, McInnis, Anisman, & Matheson, 2018), and help to overcome depression (Cruwys et al, 2013;, eating disorders (McNamara & Parsons, 2016), social anxiety (Haslam, Cruwys, Haslam, Dingle, & Chang, 2016), and substance use (Best et al, 2016;Dingle, Cruwys & Frings, 2015). In support of key social cure theorising, in Chapter 4, using qualitative interviews with participants of the ABG, we found that participants reported their group membership meeting psychological needsbelonging, self-efficacy, purpose, and positive emotions.…”
Section: The Social Cure In Arts-based Groupsmentioning
confidence: 99%